Ciclo de vida domiciliar, ciclo do lote e mudança no uso da terra na Amazônia rural brasileira: um estudo de caso para Altamira, Pará - Gilvan Ramalho Guedes (2010)
This study examines the ability of life cycle theory to predict land use and cover change in agricultural frontiers characterized by the growing influence of regional institutions and markets. Based on this post-frontier scenario, we propose a revisited life cycle model of land use/cover change, which suggests the declining influence of life cycle variables on land use strategies among rural households exposed to market influences. Furthermore, our model suggests an interaction between life cycle and lot cycle in influencing land use change. That is, the longer a households time in the frontier, the smaller the influence of life cycle indicators on land use change in consolidated agricultural frontiers. To test the proposed model, we use data from different sources and of different types: a) panel data on 402 rural lots in a settlement area near Altamira, Pará, interviewed in 1997/1998 and revisited in 2005; c) property sketch maps and its associated land use systems; c) semi-structured interviews with selected property owners, and d) land cover based on remote sensing of the 402 surveyed rural lots, for 1996 and 2005.We find that life and lot cycle indicators do not adequately predict land use/cover change in our study site. To the contrary, they lose significance when exogenous drivers of land cover change, such as biophysical characteristics, social and familial networks and integration to markets, are added to the models. We also find some evidence of declining influence of life cycle indicators on land use strategies as rural households increase time on the lot - a proxy of exposure to frontier environment. Finally, the increasing level of connection to surrounding urban areas and family migration seem to be strategic responses to credit constraints, allowing rural households to invest financial remittances in commercial crops, compensating for the loss of family labor. Household life cycle and lot life cycle, therefore, show limited ability to predict land use trajectories in frontiers characterized by complex livelihood strategies and growing influences of forces beyond the boundaries of the rural households and their lots.